Islamic Economic Value: Social Capital of Coffee Farmers for Household Welfare in Bukit Kemuning District, North Lampung Regency - Melani Melani; Ghina Ulfah Saefurrohman; Alief Rakhman Setyanto (LPPM Universitas Buddhi Dharma, 2026)
This research is motivated by the importance of social capital in supporting the economic sustainability and welfare of coffee farmers' households in Bukit Kemuning District, North Lampung Regency, especially in the midst of the challenges of coffee price fluctuations, high production costs, and limited access to economic institutions. This study aims to find out the dynamics of the social capital of coffee farmers, strategies for increasing social capital and household welfare, as well as Islamic economic views in optimizing the social capital of coffee farmers. This study uses a qualitative research method with a fenomenologis approach through observation, interview, and documentation techniques of 11 coffee farmer informants. The results of the study show that the social capital of coffee farmers is still relatively strong, especially in the aspects of trust, social networks, norms and social values such as mutual cooperation, mutual help, and cooperation between farmers. This social capital helps to strengthen social solidarity and support agricultural activities, although it has not fully improved economic well-being due to low coffee prices, high fertilizer prices, and weak formal economic institutions. The strategy of increasing social capital can be carried out through strengthening farmer groups, increasing cooperation between farmers, expanding market access, and government support. From an Islamic economic perspective, the values of ta'awun, ukhuwah, and amanah are important foundations in building social capital that is able to support the welfare of farmers' households in a sustainable manner.